Building Block Analysis of ATIII Affinity Fractions of Heparins: Application to the ATIII Binding Capacity of Non-conventional 3-O-Sulfated Sequences - Mourier, Pierre (Frontiers in Medicine, 2022)
In heparin, some 3-O-sulfated sequences do not meet the structural requirements of the ATIII binding pentasaccharide. These “non-conventional” sequences are the object of this study. In a previous paper (Mourier P. Heparinase digestion of 3-O-sulfated sequences: selective heparinase II digestion for separation and identification of binding sequences present in ATIII affinity fractions of bovine intestine heparins), we demonstrated that unsaturated 3-O-sulfated disaccharides detected in exhaustive heparin digests were specifically cleaved by heparinase I. Consequently, building blocks analyses of heparins using heparinases I+II+III digestion could be compared with experiments where only heparinase II is used. In these latter conditions of depolymerization, the 3-O-sulfated sequences digested into unsaturated 3-O-sulfated disaccharides with heparinases I+II+III, were heparinase II-resistant on their non-reducing side, resulting in longer new building blocks. These properties were used to study the structural neighborhood of these 3-O-sulfated moieties, which have still-undefined biological functions. In this part, heparinases I+II+III and heparinase II digestions of porcine mucosa, bovine mucosa and bovine lung heparins were compared in six fractions of increasing affinity for ATIII. Tagging of building blocks by reductive amination with sulfanilic acid was used. The distribution of 3-O-sulfated building blocks in the ATIII affinity fractions was used to examine the ATIII binding of these sequences.